2011
DOI: 10.3727/096504011x12935427587803
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclooxygenase-2 Inhibitor Celecoxib Attenuates Hepatocellular Carcinoma Growth and c-Met Expression in an Orthotopic Mouse Model

Abstract: To demonstrate in vivo tumor growth inhibition, the liver cancer cell lines HepG2, BEL7402, and SMMC7721 were independently inoculated into the livers of 45 6-week-old nude mice. After 24 h, mice were randomly divided into celecoxib (intragastric celecoxib suspension, 300 mg/kg), negative control (equal volume intragastric saline), and positive control (intraperitoneal injection of 6 mg/kg doxorubicin) and treated once per day for 3 days. Body weights, tumor diameters, and tumor expressions of proliferating ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It has been demonstrated in vivo and in vitro that the expression of COX-2 is associated with the proliferation and metastasis of tumor cells (22). In addition, COX-2 has been proposed as a potential pharmacologic target to decrease the growth of certain human tumors (23). Previous studies identified that the expression of COX-2 was upregulated in GC and may be targeted by miR-143 (24,25), which suggests that targeted COX-2 by miRNA may serve as a novel approach for the treatment of GC.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated in vivo and in vitro that the expression of COX-2 is associated with the proliferation and metastasis of tumor cells (22). In addition, COX-2 has been proposed as a potential pharmacologic target to decrease the growth of certain human tumors (23). Previous studies identified that the expression of COX-2 was upregulated in GC and may be targeted by miR-143 (24,25), which suggests that targeted COX-2 by miRNA may serve as a novel approach for the treatment of GC.…”
Section: Introductionmentioning
confidence: 99%
“…Existing literature indicates that a COX-2-specific inhibitor could suppress tumor growth both in vitro and in an HCC animal model. However, all these inhibitors have not yet been clinically applied (28,29). Researchers have found that COX-2 inhibitors could adversely affect cardiovascular and renal functions (30).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that celecoxib, a selective inhibitor of COX-2, at the concentration of 20 mM, enhanced the cytotoxic effects of anti-cancer agents (doxorubicin, 5-fluorouracil, sorafenib or gefitinib) on HepG2 cells (Roy et al, 2010;Cui et al, 2014). Furthermore, celecoxib effectively suppressed the in vivo growth of liver cancer in an orthotopic tumor model (Yin et al, 2011). Therefore celecoxib was used in oleuropeintreated HepG2 cells.…”
Section: Oleuropein Released Ca 2þ From the Endothelium (Er) In Hepg2mentioning
confidence: 99%